On new collections of Scaphidiinae (Coleoptera: Staphylinidae) from China, with description of two new species - Löbl, Ivan (Zootaxa, 2022)
Two new species of Scaphidiinae, Scaphisoma konvicka sp. nov. and Toxidium hartmanni sp. nov. are described from China. New records are given for eight other Chinese scaphidiine species.